Timing characterisation of TelePix2 - Augustin, Heiko; Dittmann, Lucas; Huth, L.; Immig, David; Kolb, Ruben; Perić, I.; Schöning, André; Sefkow, F.; Stanitzki, M.; Weinläder, Benjamin; Wintle, A. (Journal of Instrumentation, 2025)
The DESY II Test Beam Facility offers electrons with a user-selectable energy from 1-6 GeV primarily for detector characterisation. TelePix2, an HV-CMOS sensor, is new user-infrastructure at the test beam facility used as a Region of Interest (ROI) trigger for efficient small prototype testing and a timing plane for ambiguity suppression. Here, timing characterisation results of TelePix2 are presented. A time resolution of σ = 3.75(1) ns was determined at an efficiency above 99% at a depletion voltage of -85 V. Further timing improvements 𝒪(0.1 ns) were achieved through offline corrections for delays dependent on hit position and time-walk. A time resolution of σ = 2.216(3) ns from the signal of TelePix2 that can be used as a trigger was determined.
Veröffentlicht: 27. Juni 2025
Gesehen am 31.10.2025